PROTOTIPE PENDINGIN PERANGKAT TELEKOMUNIKASI SUMBER ARUS DC MENGGUNAKAN SMARTPHONE - Jaenal Arifin; Intan Erlita Dewanti; Danny Kurnianto (PSTE UNIMUS, 2017)
The problem of telecommunication device in BTS shelter typically hot, up and drop voltage. The damage of telecommunication device will interrupt communication between receiver and transmitter. This final project proposes a benefit for telecommunication device in order to maintain the temperature of telecommunication device appropriate with the function. This dc cooler for telecommunication device can work automatically using Arduino Uno.This tool utilizes work princip of a peltier element which has the side absorb heat and removing heat and can be supplied by direct current as voltage source. The normal temperature of telecommunication device ranged from 22oC until 26oC. When the temperature of the telecommunication device exceeds normal temperature thenthis tool will be active and when the temperature of the telecommunication device is back to normal then this tool will be automatically off. The temperature of the telecommunication device also can monitored by LCD and smartphone with Bluetooth as media. DHT11 sensor in this tool can work well with error 2,71%. The LCD can display characters letters and numbers when given input voltage 3.9volt and Bluetooth can connected at distance less than 15 metres without the obstacle and at distance less than 4 meters when there are obstacle. Keywords: Arduino Uno, Peltier, Bluetooth, Telecommunication Device